Trace elements in Brazilian soils. - Rocha, Geraldo Cesar (Semina: Ciências Agrárias, 1995)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> A literature revision on trace elements (Zn, B, Mn, Mo, Cu, Fe and Cl) in Brazilian soils was prepared, with special attention to the chemical form and range in the soil, extraction methods and correlation of the amount in soils with soil properties